2016
DOI: 10.1002/jhm.2607
|View full text |Cite
|
Sign up to set email alerts
|

Comparing three different measures of frailty in medical inpatients: Multicenter prospective cohort study examining 30‐day risk of readmission or death

Abstract: BACKGROUND Multiple tools are used to identify frailty. OBJECTIVE To compare the global Clinical Frailty Scale (CFS) with more objective phenotypic tools (modified Fried score and the Timed Up and Go Test [TUGT]). DESIGN Prospective cohort study. SETTING General medical wards in Edmonton, Canada. PARTICIPANTS Adults being discharged back to the community. MEASUREMENTS All frailty assessments were done within 24 hours of discharge. Patients were classified as frail if they scored ≥5 on the CFS and/or ≥3 on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…26 Similarly, after classification of 72 older patients undergoing colorectal surgery on the basis of 7 frailty traits, 30-day readmission rates rose with increasing frailty from 6% to 29%. 27 Among nonsurgical patients, a Clinical Frailty Scale score of 5 or higher independently predicted a threefold risk of 30-day readmission or death among 245 older medical patients 17 and a twofold risk of 1-year readmission among 421 critically ill older patients. 5 In this study, we overcame several limitations of prior studies by enrolling an older but largely unselected surgical cohort and reporting outcomes that occurred as long as 6 months after discharge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Similarly, after classification of 72 older patients undergoing colorectal surgery on the basis of 7 frailty traits, 30-day readmission rates rose with increasing frailty from 6% to 29%. 27 Among nonsurgical patients, a Clinical Frailty Scale score of 5 or higher independently predicted a threefold risk of 30-day readmission or death among 245 older medical patients 17 and a twofold risk of 1-year readmission among 421 critically ill older patients. 5 In this study, we overcame several limitations of prior studies by enrolling an older but largely unselected surgical cohort and reporting outcomes that occurred as long as 6 months after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…However, we enrolled a diverse cohort and we were more interested in less severely frail patients who are amenable to preventive strategies. Although we did not compare different tools or assess more objective frailty measures, we selected a frailty tool that is easy to use, reliable and predictive of clinically relevant outcomes, [16][17][18] and that has been recommended for use in other surgical populations. 13 We did not assess long-term disability or quality of life, which may be of particular importance to clinicians and patients.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found independence rates between 15 and 73% at this time point 5,16,17 . The rates can differ depending on the population studied and the research location, as was found in a study that found a prevalence of independence in BADL of 75% in patients aged over 55 years 5 and another that evaluated the elderly aged over 65 years and study that evaluated the elderly based on two sets of criteria, the CFS and Fried, found that frailty was related to a loss of functional capacity and worse outcomes, such as hospital readmission and death 23 . As in previous studies, it was observed that frailty, evaluated by the Fried criteria, was associated with a loss of functionality.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of frailty is described as a risk factor for loss of functional capacity, hospitalization and death in the elderly living in the community 21,22 and death in hospitalized elderly persons 23 . Gregorevic et al 24 , using the Clinical Frailty Scale (CFS) in the evaluation of frailty in hospitalized elderly persons, observed that frail elderly individuals had a greater risk of functional loss, post-discharge institutionalization and death.…”
Section: Discussionmentioning
confidence: 99%